The role of proverbs in Chilndren's and Young Adult Literature: a semantic-literary approach to two Spanish publications - Negrete-Portillo, Rafael (Romanica Olomucensia, 2024)
The aim of this paper is to demonstrate that proverbs can be seamlessly incorporated into literary texts for a young readership without necessitating adaptations of the plot or distorting narrative structures. With this aim all the proverbs identified in two highly successful stories targeted at children and adolescents were extracted: El sabio Marut, for ages six and up; and Antes de medianoche, for ages ten and up, both written by Ana Alonso. Afterwards, the proverbs were classified semantically, partly following the thematic proposal of Mª Josefa Canellada and Berta Pallares, partly that of the Refranero multilingüe. Finally, their literary relevance was interpreted. The 12 proverbs that were studied denote truth (four proverbs), advice (two proverbs), appearances (one proverb), character (two proverbs), hierarchy and authority (one proverb), and consequence (two proverbs). El sabio Marut, despite being aimed at a younger readership, has two more proverbs (seven) than Antes de medianoche (five). The study appears to demonstrate the feasibility of crafting narratives that pivot around proverbs, thereby naturalising their usage within a credible communicative context for the readership of Children's and Young Adult Literature (CYAL) to whom the books under analysis are addressed.
Keywords: Children's and Young Adult Literature (CYAL); narrative; literary competence; applied paremiology; semantic classification